HUBUNGAN STATUS GIZI DAN KEBIASAAN MEROKOK DENGAN KEBUGARAN JASMANI PETUGAS PEMADAM KEBAKARAN BPBD KOTA DENPASAR - Purwaningsih, Ni Nyoman Ari; Sutiari, Ni Ketut (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 3 (2022): Desember 2022DO - 10.24843/ACH.2022.v09.i03.p08, 2022)
ABSTRACT Physical fitness is an important health indicator for workers because it is related to their physical ability to work optimally. Physical fitness is influenced by several factors including nutritional status and smoking habits. This study aims to determine the relationship between nutritional status and smoking habits with physical fitness on firefighters at BPBD Denpasar. This study is a quantitative study with a cross-sectional design. This study used total sampling and found 75 firefighters who work at BPBD Denpasar as the sample. Data were analyzed using chi square test. The results of this study showed that more than half of the firefighters were in the unfit category (57.3%), most of the respondents belonged to the fat category BMI (69.3) and normal abdominal circumference (56%) and the majority of firefighters had a smoking habit (80%). Based on bivariable analysis, it was found that there was a significant relationship between nutritional status based on BMI (p=0.0012) and abdominal circumference (p=0.0003) with physical fitness, but there was no significant relationship between smoking habit and physical fitness (p=0 ,3808). By this study, the researcher recommended that firefighters should keep their physical fitness by physical activity and control eating patterns. Keywords: Physical Fitness, Nutritional Status, Smoking Habits, Firefighters.